STRATEGI DIFERENSIASI: UPAYA MENCIPTAKAN KEPUASAN NASABAH (Studi Kasus pada Bank Muamalat Cabang Palembang) - Yusi, M. Syahirman (JURNAL KEBANGSAAN, 2012)
The purpose of this research is to find out the influence of differentiation strategy on costumerâs satisfaction. According to theory variable of differentiation strategy that can increase the customerâs satisfaction are productâs differentiation, serviceâs differentiation and imageâs differentiation. Data was collected through interview and questionaires were distributed to 100 respondents and was analyzed with SPSS for windows. The conclusions were simultaneously significant effect on differentiation strategy by the value of costumerâs satisfaction 67,89%, F test was 28,4265 and sig. 000, but partially only one ariable that had most dominant variable that can give more influence to increase the costumerâs satisfaction, that was reputation in image differentiation of company, the value of test was 8,694 and sig. 000.